Metamaterial Antennas for RADAR and SAR - Bruno Filipe Oliveira Correia (2018)
RADAR and Synthetic Aperture Radar (SAR) system require broadband directive antennas. Directivity require antennas to be large, which turns to be impracticable in many applications. Metamaterial antennas are built using complex miniaturized structures that produce small antennas that behave equally to much larger traditional antennas. The goal of this dissertation is to obtain a small antenna array based on small antennas with such properties, in order to obtain a directive and broadband antenna suitable for RADAR and SAR operation.